Epidemiology and Control of diabetes - tuberculosis comorbidity in Eswatini: protocol for the prospective study of tuberculosis patients on predictive factors, treatment outcomes and patient management practices - Diederick E Grobbee; Kerstin Klipstein-Grobusch; Kennedy Otwombe; Victor Williams; Alinda Vos (BMJ Open)
Introduction Previous studies indicate people with diabetes mellitus (DM) may have varying treatment outcomes when receiving treatment for tuberculosis (TB) and that TB infection or its treatment may predispose them to develop an abnormal blood glucose or type 2 DM. This has implications for Eswatini which is a high TB burden country and with increasing cases of non-communicable diseases including DM. This study will describe the epidemiology of DM-TB comorbidity in a prospective cohort of patients receiving TB treatment and identify best practices for integration of care for non-communicable diseases into TB services in Eswatini.Methods and analysis This study will employ a mixed-methods approach. Data from a prospective cohort of newly enrolled patients with TB at 12 health facilities from 1 June 2022 to 30 September 2022, and followed up to 30 April 2023, will be used. For the qualitative, key informants who provide TB services at the health facilities will be interviewed. Quantitative data from patients will be analysed descriptively and by tests of association and multivariate modelling. Key informant interviews from healthcare workers will be analysed using content analysis.Ethics and dissemination This research has been approved by the Eswatini Health and Human Research Review Board and participant confidentiality will be maintained. COVID-19 safety measures to reduce the risk of infection or transmission by researchers and participants have been instituted. Key programmatic findings and how they can impact healthcare delivery and access will be presented to the specific programme in the Eswatini Ministry of Health and other relevant stakeholders.